2016
DOI: 10.1126/science.aah5234
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain dopamine neurons control judgment of time

Abstract: Our sense of time is far from constant. For instance, time flies when we are having fun, and it slows to a trickle when we are bored. Midbrain dopamine neurons have been implicated in variable time estimation. However, a direct link between signals carried by dopamine neurons and temporal judgments is lacking. We measured and manipulated the activity of dopamine neurons as mice judged the duration of time intervals. We found that pharmacogenetic suppression of dopamine neurons decreased behavioral sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
290
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(320 citation statements)
references
References 40 publications
18
290
1
1
Order By: Relevance
“…Similar to the current study, the authors found that the population dopamine neuron activity, reflected by calcium signals recorded through optic fibers, is associated with trial-by-trial variability in behavioral performance, and that optogenetic stimulation of dopamine neurons alters psychometrics of behavioral choice (Soares et al, 2016). Interestingly, both studies have found that driving dopamine activity increases, rather than decreases short-duration selection (Figure 6 and Figure S8) (Soares et al, 2016), at odds with the so-called dopamine clock hypothesis in the timing literature that predicts increased dopamine release would speed up the internal clock (Buhusi and Meck, 2005; Simen and Matell, 2016). The authors also report changes in dopamine are tightly associated with behavioral choice in their task, highlighting a potential role for dopamine in action selection (Soares et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to the current study, the authors found that the population dopamine neuron activity, reflected by calcium signals recorded through optic fibers, is associated with trial-by-trial variability in behavioral performance, and that optogenetic stimulation of dopamine neurons alters psychometrics of behavioral choice (Soares et al, 2016). Interestingly, both studies have found that driving dopamine activity increases, rather than decreases short-duration selection (Figure 6 and Figure S8) (Soares et al, 2016), at odds with the so-called dopamine clock hypothesis in the timing literature that predicts increased dopamine release would speed up the internal clock (Buhusi and Meck, 2005; Simen and Matell, 2016). The authors also report changes in dopamine are tightly associated with behavioral choice in their task, highlighting a potential role for dopamine in action selection (Soares et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Previously, dopamine has been implicated in timing behaviors (Buhusi and Meck, 2005;Oleson et al, 2014), mostly based on results of pharmacological experiments with global manipulation, though it remains unclear whether these effects resulted from altering time perception or because of disrupted action selection. A recent study by Soares et al (2016) utilized a temporal discrimination task to determine the contribution of midbrain dopamine to interval duration judgment. Similar to the current study, the authors found that the population dopamine neuron activity, reflected by calcium signals recorded through optic fibers, is associated with trial-by-trial variability in behavioral performance, and that optogenetic stimulation of dopamine neurons alters psychometrics of behavioral choice (Soares et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have provided direct evidence for a representation of time in the striatum that is distributed over a set of neurons (49,50) and that DA neurons may directly modulate timing (47). The specific set of functions adopted in our work (43,51) is a possible realization of these findings.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to this negative slow modulation, we found that also the DA phasic activation at the go cue depends on the duration of the temporal interval preceding it, resulting in a stronger response for long intervals. While some previous results appear not to be in contradiction with this pattern of phasic activation (46), other studies (25,32,47) reported an opposite trend (stronger response for short intervals). Here we propose an explanation for this discrepancy: The size of the response to the go cue is determined by the hazard of occurrence of this event and by the finite resolution in the estimation of the elapsed time, which is worse for long (as in our work) than for short intervals (as, e.g., in ref.…”
Section: Discussionmentioning
confidence: 62%